HYPOTHETICAL LEARNING TRAJECTORY (HLT) BABAT DALAM PROSES PEMBELAJARAN MATEMATIKA DI KELAS III : IMPLEMENTASI RME BERBASIS ETNOMATEMATIKA MELALUI MAKANAN KHAS DAERAH (WINGKO) - Nur rachma Sastra pradita; Neni Mariana (Universitas Negeri Surabaya, 2022)
Mathematics is a scientific discipline, learning mathematics is a mandatory learning that is taught to students. However, not a few students stated that they did not like mathematics because they thought mathematics was difficult. In fact, learning mathematics actually brings many benefits and advantages that will be felt later when they grow up and live real life. It turns out that in reality learning mathematics in Indonesia still uses an approach that is less meaningful, rigid, and unattractive to students. In fact, we have to meet the demands of 21st Century learning. For this reason, researchers conducted research on ethnomathematics-based Hypothetical Learning Trajectory (HLT) RME through regional specialties, namely wingko tripe in the process of learning mathematics in class III SD. This research aims to make mathematics learning more meaningful, interesting, and not boring for students. This study uses the Design and Research method. This study proves that using the Hypothetical Learning Trajectory (HLT) can help students understand the learning trajectory to understand the material angles with the media in the form of concrete objects, namely wingko, can create more meaningful, interesting, and not boring mathematics learning.